A Day of Hunger - Javier Fernández Álvarez (Universidad de Alicante, 2016)
My experience as a volunteer in Africa made me reflect on the importance of the death of a child and look for different situations and cultures. In European society, we assume that parents should outlive their children and who would die for their children. In Ethiopia where families can not afford to make a minimum contribution of food needed, mothers come in such bad shape that they are unable to give breastfeeding, and people are accustomed to the early years are the most critical, the most difficult, as they are accustomed to losing in those years to his brothers, sons, grandsons, nephews and friends.